(untitled) (International Journal of Ayurveda and Pharma Research, 2019)
Children with the clinical features of Chronic Tonsillitis coming under the age group 3-12 years were included in the study. The patients were randomly allocated in to the study group and control group using simple random sampling technique. In the study group the dose of Varabrihatyadi Kashaya was fixed as follows, in the age group 3-6 years: 10ml bd before food, in the age group 6-9 years: 20ml bd before food, in the age group 9-12 years: 30ml bd before food. Sarapunkha lepa was applied around the neck where enlarged lymph nodes were found. Frequency of paste was fixed as two times daily and at each time, it is kept until it becomes dry. At the same time those in the control group were subjected to external application of Sarapunkha lepa only. Both the groups were followed for a period of 1 month after the scheduled course of intervention. Routine blood investigations were also carried out before and after the study. The data were analyzed using the most appropriate statistical tests. Significant changes were obtained in the clinical parameters in the study group used for assessment such as recurrent attacks of sore throat, pain in the throat, pain on swallowing, difficulty in swallowing, halitosis, mouth breathing, hoarseness of voice, chocking spells at night, size of the tonsil, congestion of pillars, oedema of the uvula, deviation of the uvula and lymph node enlargement. There was a significant change in the routine blood investigations also. Moreover the trial drug sustained its potential action even during the follow up period. The effect of control drug was insignificant. The final evaluation proved that combination of Varabhrihathyadi Kashaya and Sarapunkha lepa was effective in reducing the signs and symptoms of Chronic Tonsillitis in children of 3-12 yrs age group.